COVID-19 in Immunosuppressed Children - Nicastro, Emanuele; Verdoni, Lucio; Bettini, Laura Rachele; Zuin, Giovanna; Balduzzi, Adriana; Montini, Giovanni; Biondi, Andrea; D'Antiga, Lorenzo (Frontiers in Pediatrics, 2021)
Following the spread of SARS-CoV-2 infection and Coronavirus disease 2019 (COVID-19) to a global pandemic, concerns have arisen for the disease impact in at-risk population, especially in immunocompromised hosts. On the other hand, clinical studies have clarified that COVID-19 clinical burden is mostly due to overinflammation and immune-mediated multi-organ injury. This has led to downsize the role of immunosuppression as a determinant of outcome, while early reports have confirmed the hypothesis that patients undergoing immunosuppressive treatments do not have an increased risk of severe COVID-19 with respect to general population. Intriguingly, SARS-CoV-2 natural reservoirs such as bats and mice have evolved mechanisms of tolerance involving selection of genes optimizing viral clearance through interferon type I and III responses, but also dampening inflammasome response and cytokine expression. Children exhibit resistance to COVID-19 severe manifestations possibly involving age-related mechanisms of induction of regulatory T lymphocytes and reduction of innate-response signaling molecules, similar to what has been documented in other models of viral infections. A competent recognition by the innate immune system and a controlled proinflammatory signaling seem to be the pillars of an effective response and the premise for pathogen clearance in SARS-CoV-2 infection. Immunosuppression – if not associated with other elements of fragility – do not represent per se an obstacle to this competent/tolerant phenotype in children. Several reports confirm that children receiving immunosuppressive medications have similar clinical involvement and outcomes as the pediatric general population, indicating that maintenance treatments should not be interrupted in suspect or confirmed SARS-CoV-2 infection.